A role of Werner helicase interacting protein 1 in the Fanconi Anemia DNA repair pathway - Socha, A (2017)
This doctoral thesis investigates whether Werner Helicase Interacting Protein 1 (WRNIP1) is involved in the Fanconi Anemia (FA) pathway. The FA pathway is responsible for resolving DNA interstrand crosslinks (ICLs). While the exact mechanism is unknown, there are 21 confirmed proteins that belong to the pathway, and they can be all divided into three functional groups: the core complex, the FANCD2-FANCI complex and downstream effector proteins. It was demonstrated here that WRNIP1 depletion results in higher sensitivity to cross-linking agents (Mitomycin C (MMC) and UVA light after trioxalen (TMP) sensitization). The complementation of WRNIP1 – null cell lines with WRNIP1-EGFP resulted in sensitivity comparable with the wild type cell line. It was also shown in vivo that WRNIP1-EGFP is recruited to the chromatin, after TMP-UVA treatment, within first five minutes after irradiation. It was also demonstrated that WRNIP1 is recruited before FANCD2 and that while FANCD2 depletion does not affect WRNIP1 recruitment in any way, WRNIP1 depletion slightly reduces the levels of FANCD2 recruitment, which suggests that WRNIP1 acts upstream from FANCD2. Since WRNIP1 migrates on the SDS-PAGE gel as two species, the upper form, was analysed and confirmed as ubiquitinated WRNIP1. It was then purified and analysed with mass spectrometry, which allowed the identification of several potential ubiquitination sites. None of the found residues was shown to be the necessary for WRNIP1 upper form to appear and none of them was crucial for WRNIP1 recruitment to the ICL damage site. To further investigate the roles of each of the domains found within the structure of human WRNIP1, each of the domains was abrogated using one specific point mutation designed to disrupt the function of the whole domain or motif. The analysis of WRNIP1-EGFP point mutants have shown that UBZ domain is responsible for WRNIP1 ubiquitination and while its activity is abrogated, WRNIP1-EGFP is not recruited to the damage site. Finally, it was confirmed that WRNIP1 interacts in vitro with FANCD2, and the analysis of the deletion mutants have shown that none of the deleted sequences was alone necessary for this interaction. The similar analysis performed with WRNIP1 divided into five short fragments, suggests that the sequence between 370 and 510 aa participates in WRNIP1-FANCD2 binding, though it is not conclusive if it is the only part of WRNIP1 that is participating in this interaction.